APPLICATION OF ICT IN THE AREA OF VIRTUAL ARCHAEOLOGY FOR STUDENTS WITH SPECIAL EDUCATIONAL NEEDS IN THE STAGE OF COMPULSORY SECONDARY EDUCATION - J. Durga Prasad Rao, Hari Shankar Prasad Tonde, Prachi Sharma (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Today’s culture is persuaded that quality schooling must enter all young people, beyond exemption. In this context, particular focus is put on the variety of students in the ESO. Adequate preparation can contribute to greater ersonal and social growth, such that students will transition into an increasingly challenging society. Modern Information and Networking Systems promote teaching-learning cycles in this sense. A few of them, Archeology Virtual, allows it possible to turn heritage artifacts into real and powerful instruments at the disposal of the school and, ultimately, of society.